2016
DOI: 10.3126/ijasbt.v4i1.14557
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Approach of Structure Prediction and Functional Characterization of Zaire Ebola (Ebov) and Identification of Binding Site for Drug Development

Abstract: Zaire ebolavirus (EBOV) is one of the dangerous and a negative-stranded ssRNA virus. EBOV is a zoonotic pathogen that causes severe hemorrhagic fever in humans. Nowadays epidemic outbreak caused by EBOV is incurable with present technologies; thus figure out as a major health risk which needs enhanced surveillance. The study was conducted with seven proteins of Zaire ebola (EBOV) and gene sequences are available in NCBI database. The homology modeling was done by SWISS-MODEL, Phyre2 and HHpred. The obtained mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, the authors failed to provide details concerning active site residues. The predicted active site of the RdRp of the EboV was generated using the CASTp server as indicated in a study by Islam et al (2016), however, active site residues were also not reported there.…”
Section: Reported Studies On Active Site Identification Of Ebov Targetsmentioning
confidence: 99%
“…However, the authors failed to provide details concerning active site residues. The predicted active site of the RdRp of the EboV was generated using the CASTp server as indicated in a study by Islam et al (2016), however, active site residues were also not reported there.…”
Section: Reported Studies On Active Site Identification Of Ebov Targetsmentioning
confidence: 99%